INTRODUCING A LIFE ASSURANCE GUARANTEE SCHEME IN UKRAINE: FUNDING MECHANISM AND RISK-BASED ADJUSTMENT - O. Shevchuk; N. Yaroshevych; L. Yevtukh (Фінансово-кредитна діяльність: проблеми теорії та практики, 2021)
Abstract. Life insurance, as well as bank deposits, is a form of household savings, so contributions under life insurance contracts must be properly guaranteed by creating compensation mechanism. The paper deals with a number of issues in relation to the solutions for Ukrainian life insurance guarantee scheme (IGS). The main purpose of this study is to introduce decision on scheme design and appropriate fund-raising mechanism for Ukrainian IGS providing the last resort protection to customers who make their savings via life assurance contracts. Highlighting positive and negative effects of IGS implementation, analysing sources of funding for guarantee schemes, the research substantiates economic effects of risk-based approach to assessing contribution and proposes general scheme of estimating the insurer’s contribution to the IGS fund, in particular indicators for risk-based adjustment of IGS levies and adjustment procedures.